Perancangan Sistem Informasi Penjualan Sepatu Menggunakan Microsoft Visual Basic 6.0 Puji Astuti - Astuti, Puji (Indonesian Journal on Software Engineering (IJSE), 2018)
Abstrac - The rapid advancement of science and technology increasingly encourages people to improve and even create a new technology that benefits humans. Computers are one proof of technological advancement today. Not all businesses are already using computerized systems. In this study the authors looked directly at people who have small businesses or medium enterprises in the sale of shoes still manually. So it is necessary to create a good information system and useful for the sale of shoes by using Microsoft Visual Basic 6.0. data collection method used is observation and literature study. Software development methods used starting from the needs analysis, system design and software and implementation of systems and software. Making this sales application by using Microsoft Visual Basic 6.0, storage using Microsoft Access and Crystal Report as a media report generation. The results of the preparation of this writing in the form of a computerized application system in the sale of shoes, resulting in reports sales transactions are faster, precise, effective, and accurate. Keywords: Microsoft Visual Basic 6.0, Sales System